2017
DOI: 10.2196/jmir.5998
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Measurement Properties of the eHealth Literacy Scale (eHEALS) Among Baby Boomers: A Multinational Test of Measurement Invariance

Abstract: BackgroundThe eHealth Literacy Scale (eHEALS) is one of only a few available measurement scales to assess eHealth literacy. Perhaps due to the relative paucity of such measures and the rising importance of eHealth literacy, the eHEALS is increasingly a choice for inclusion in a range of studies across different groups, cultures, and nations. However, despite its growing popularity, questions have been raised over its theoretical foundations, and the factorial validity and multigroup measurement properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
176
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(204 citation statements)
references
References 84 publications
(200 reference statements)
20
176
8
Order By: Relevance
“…This suggests that eHEALS scores can be interpreted equivalently, regardless of respondents' age group membership. Despite invariance between groups in the current sample, Sudbury-Riley and colleagues [39] found an inconsistent number and type of items comprising each of the factors. An item that assessed confidence in the capacity to evaluate health information found on the Internet loaded on the health information seeking skill factor.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…This suggests that eHEALS scores can be interpreted equivalently, regardless of respondents' age group membership. Despite invariance between groups in the current sample, Sudbury-Riley and colleagues [39] found an inconsistent number and type of items comprising each of the factors. An item that assessed confidence in the capacity to evaluate health information found on the Internet loaded on the health information seeking skill factor.…”
Section: Discussioncontrasting
confidence: 58%
“…Consistent with these studies, a 3-factor model has also been confirmed among baby boomers and older adults [36], including chronic disease patients [34] and adults, with an average age of 53, in a magnetic resonance imaging and computed tomography medical imaging outpatient clinic [40]. Despite evidence for measurement invariance among middle-to-older age adults in multiple nations [39], empirical attention is needed to confirm the 3-factor structure among a general population consisting of younger and older adults. This will have important implications for eHealth practitioners and researchers to monitor eHealth literacy surveillance across the lifespan and to evaluate the efficacy of age-targeted interventions, which are primarily delivered to older adults, with a valid and reliable instrument.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations